KEWAJIBAN PARTAI POLITIK DALAM PENYELENGGARAAN EDUKASI POLITIK BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2008 TENTANG PARTAI POLITIK - Suprayoga, Tatang (ANDREW Law Journal, 2025)
Based on Article 13 Letter e of Law Number 2 of 2008 concerning Political Parties, it is stipulated that Political Parties are required to provide political education to their members and also to the community. The method used in this study is normative legal research using a statutory regulatory approach. Based on Article 1 Number 4 of Law Number 2 of 2011 concerning Amendments to Law Number 2 of 2008 concerning Political Parties, it is explained that political education is a process of learning and understanding the rights, obligations, and responsibilities of every citizen in the life of the nation and state. Political Parties provide political education for the community in accordance with the scope of their responsibilities by paying attention to gender justice and equality with the aim of: First, increasing awareness of the rights and obligations of the community in the life of society, nation, and state; Second, increasing political participation and community initiatives in the life of society, nation, and state; and Third, increasing independence, maturity, and building national character in order to maintain national unity.